The art of selection in coronary bypass grafting - Motovska, Zuzana; Akın, Ibrahim (European heart journal, 2022)
This editorial refers to ‘Single versus multiple arterial grafting in diabetic patients at 10 years: the Arterial Revascularization Trial’, by D.P. Taggart et al., https://doi.org/10.1093/eurheartj/ehac199.Aortocoronary bypass graft surgery (CABG) is the most common surgical procedure performed on the heart. For over half a century, millions of patients have undergone revascularization using this method. Improvements in surgical technique, peri-operative care, knowledge of the limitations and advantages of vascular grafts, and increased utilization of secondary preventions have led to reduced complications, in-hospital mortality, and long-term persistence of the effects of revascularization.
Online vorab veröffentlicht: 05. Juli 2022
Gesehen am 09.07.2024